2019
DOI: 10.1080/07420528.2019.1647435
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term effects of unguided internet-based cognitive behavioral therapy for chronic insomnia in morning and evening persons: a post-hoc analysis

Abstract: A post-hoc analysis comparing morning and evening persons with insomnia on sleep and mental health characteristics was conducted in order to investigate whether an Internet-based cognitive behavioral therapy for insomnia (ICBTi) was effective both for morning and evening persons. Adult patients (N=178, mean age= 44.9, 67% females) with insomnia were randomized to either ICBTi (N=92; morning persons = 41; evening persons = 51) or a web-based patient education condition (N=86; morning persons = 44; evening perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…iCBT studies could be further subcategorized based on the type of comparison that was made. Of the 18 RCT studies in this category, 6 (33%) compared iCBT against a waitlist condition [ 2 , 20 , 31 - 33 , 37 ]; 5 (28%) studies compared unguided intervention with guided controls [ 21 , 24 , 26 , 38 , 39 ]; 8 (44%) studies compared iCBT with other types of interventions [ 19 , 25 , 27 - 30 , 36 , 37 ]; 1 (6%) study used a sensor-based approach and compared it to unguided iCBT without a sensor [ 22 ]. The 3 non-RCT studies were cross-sectional studies that used a single group to assess the feasibility, accessibility, and preliminary effectiveness of iCBT programs [ 23 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…iCBT studies could be further subcategorized based on the type of comparison that was made. Of the 18 RCT studies in this category, 6 (33%) compared iCBT against a waitlist condition [ 2 , 20 , 31 - 33 , 37 ]; 5 (28%) studies compared unguided intervention with guided controls [ 21 , 24 , 26 , 38 , 39 ]; 8 (44%) studies compared iCBT with other types of interventions [ 19 , 25 , 27 - 30 , 36 , 37 ]; 1 (6%) study used a sensor-based approach and compared it to unguided iCBT without a sensor [ 22 ]. The 3 non-RCT studies were cross-sectional studies that used a single group to assess the feasibility, accessibility, and preliminary effectiveness of iCBT programs [ 23 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed significantly smaller improvement in depressive mood in E-types than in N-types, with N-types in turn showing significantly smaller improvement than M-types. In contrast, an internet-based CBTI intervention study using midlife adults by Lien et al (2019) found similar improvements in depressive mood and insomnia severity in both M-and E-types. Further exploration of the interaction between CBTIeffectiveness and chronotype is required.…”
Section: Discussionmentioning
confidence: 83%
“…Their results showed significantly smaller improvement in depressive mood in E-types then N-types, with N-types in turn showing significantly smaller improvement than M-types. In contrast, an internet-based CBTI intervention study using midlife adults by Lien et al (2019) found similar improvements in depressive mood and insomnia severity in both M-and E-types. Further exploration of the interaction of CBTI-effectiveness and chronotype is required.…”
Section: Discussionmentioning
confidence: 83%